Grapevine stilbene synthase cDNA only slightly differing from chalcone synthase cDNA is expressed in Escherichia coli into a catalytically active enzyme - Melchior, Frauke; Kindl, Helmut (FEBS letters, 1990)
Stilbene synthase is responsible for the formation of resveratrol and other stilbenes which function in grapevine as phytoalexins. A full-length stilbene synthase cDNA was prepared from grapevine mRNA and sequenced. The insert in pSV25 coding for a polypeptide with 392 amino acids was inserted into the vectors pKK233-2 and pDS12/RBSII-2, respectively. Expression of the cDNA in Escherichia coli yielded an enzyniatically active dimer exhibiting solely stilbene synthase activity. The protein was characterized by enzyme activity and Western blot analysis.